Digital Romance: Investigating The Drivers of Otome Games' Increased Popularity in China Based On "Undoing Gender" - Nie, Yunting (Journal of Education, Humanities and Social Sciences, 2024)
Otome games are virtual romance games in which the player takes on the role of a female character and interacts with several male characters. This type of game initially originated in Japan has gradually become a hit in China in recent years. "Love and Deepspace" is the latest achievement of the current domestic otome games. From their appearance to their professional status, the female characters in this game are independent and mature individuals. Also, the plot and lines are more powerful than those in previous games of the same genre where the female characters used to be delicate and vulnerable. Meanwhile, game characters do not simply display "masculinity" or "femininity" in line with their gender, and personality traits that are simply divided by gender are overridden and reshaped. Back in the real world today, more and more women are no longer constrained to marriage and family. Instead, they are enjoying a life of celibacy, free from the implicit norms imposed on women by society's "doing gender". They seek the right to freely express their feelings and have fun, and the space provided by otome video games has fulfilled their demand. Combining with Butler's theory of "undoing gender" and reflecting on the current social reality, this paper attempts to analyze how gender performs in “Love and Deepspace” and explore how the game subverts the traditional heteronormative relationship model and resists the binary opposition between men and women, thus gaining the popularity of many female players.
Keywords: Undoing Gender; otome games; female-oriented games; “Love and Deepspace”.